The Effect of Folic Acid Adjuvant on Cognitive Function on Patients with Chronic Schizophrenia - Sofa, Yulia Ratna; Wardani, Natalia Dewi; sari, Linda Kartika; Hadiati, Titis; Muflihatunnaimah, Muflihatunnaimah (Faculty of Medicine, Diponegoro University, 2022)
ABSTRACT Background: Schizophrenia is a severe mental disorder that associated with daily life and social function deterioration and could be accompanied with cognitive deficits. Meanwhile, hyperhomocysteinemia (HHcy) is the increasing homocysteine (Hcy) level which might be the one of biological factor in schizophrenia. In recent study with healthy subjects, it was known that there was a correlation between total Hcy level and cognitive function. Folic acid is part of water-soluble vitamin B and expected to have important role in oxidative stress by preventing hyperhomocysteinemia.Objective: This study aimed to elaborate the effect of folic acid adjuvant to improve cognitive function in chronic schizophrenia patients.Methods: This was a double-blinded randomized controlled trial with pre and post-test clinical trial design. This study included 32 patients in control group and 32 patients in treatment group. MOCA-INA score was examined in all subjects on the first day. Then, all subjects were given standard antipsychotic treatment plus folic acid adjuvant / placebo during 3 week of hospitalized treatment and 1 week of outpatient treatment. When the 4-week treatment finished, the subjects were followed by MOCA-INA post-test.Results: In this study, we had the significant difference of pre and post-test MOCA-INA score in the control group (p<0.001), significant difference of pre and post-test MOCA-INA score in the treatment group (p<0.001), and significant difference of post-test MOCA-INA score between the control and treatment group (p<0.001).Conclusion: Folic acid adjuvants significantly improved cognitive function in chronic schizophrenic patients.